The Effect of the Pandemic on the RMG Export of Bangladesh: Exploring the Economic Channels of Transmission - Banna Banik (Managing Global Transitions, 2023)
This study aims to empirically analyse the potential long-run and short-run effects of the COVID-19 pandemic on the ready-made garments (RMG) export growth of Bangladesh. We distinguish two transmission channels: credit growth and degree of openness to trade, through which the pandemic could affect the RMG export, using monthly time series data from June 2009 to August 2020. We employ a bounds test approach to the autoregressive distributed lag (ARDL) cointegration method. The bounds test specifies long-run and short-run relationships between credit growth, openness, and RMG exports. We found that the pandemic has a significant negative effect in the short run but a positive impact on export through these transmission channels in the long run. Thus, more credit support to this sector and opening up the economy for international trade is essential for the total recovery of the RMG export.